Nanoencapsulation of the omega-3 EPA:DHA 6:1 formulation enhances and sustains NO-mediated endothelium-dependent relaxations in coronary artery rings and NO formation in endothelial cells. (December 2021) - Remila, L.; Belcastro, E.; Guenday-Tuereli, N.; Park, S.; Houngue, U.; Vandamme, T.; Tuereli, E.; Kerth, P.; Auger, C.; Schini-Kerth, V.
Graphical abstract: Highlights: Omega-3fatty acids stimulate the endothelial formation of vasoprotective nitric oxide. EPA:DHA 6:1 nanoparticles caused greater sustained endothelium-dependent relaxation. EPA:DHA 6:1 nanoparticles caused sustained formation of NO in endothelial cells. EPA:DHA 6:1 nanoparticles-treated endothelial cells had greater anti-platelet effect. Abstract: The eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) formulation with a ratio of 6:1 is a potent stimulator of the endothelial formation of nitric oxide (NO). The aim of the study was to investigate whether nanoencapsulation of EPA:DHA 6:1 followed by coating with gum increases its biological activity. Vascular reactivity was assessed using porcine coronary artery rings, the formation of NO in cultured endothelial cells (ECs) using DAF-FM and indirectly by platelet aggregation studies. Coated EPA:DHA 6:1 nanoparticles induced sustained relaxations of coronary artery rings that were greater in rings with than in those without endothelium, and more pronounced than with the native form. Treatment of ECs with coated EPA:DHA 6:1 nanoparticles caused greater and more sustained formation of NO and enhanced their anti-aggregatory effects. Thus, nanoencapsulation of EPA:DHA 6:1 is an attractive strategy to enhance the beneficial effect at the vascular endothelium.